Telehealth and Physical Therapy Clinical Decision Making in a Patient with a Falcine Meningioma - Ryan Boggs; Nicholas Frappa; Michael Ross; Michael Tall (International Journal of Telerehabilitation)
Telehealth utilizes information technologies and communication networks to deliver healthcare and education with lower costs and improved access, quality, and efficiency of healthcare services.  This report describes the application of telehealth for medical screening, clinical decision making, and medical referral in a physical therapy practice. The patient described was a 50-year old man who contacted his physical therapist via telephone for a chief complaint of worsening left sided numbness and tingling that began insidiously 2 days prior.  Further questioning revealed that the patient also complained of left ankle weakness, and slight unsteadiness with walking. He had not been feeling well and had been experiencing increasing bouts of unexplained fatigue over the previous two months that were now interfering with his work and recreational activities. The patient was evaluated by his physician the next day.  Magnetic resonance imaging of the brain revealed a large (4 cm) falcine meningioma in the right parietal region.  The patient was immediately referred to a neurosurgeon and underwent a craniotomy and tumor resection ten days later and subsequent gamma knife radiosurgery of the residual tumor bed two months after craniotomy and tumor resection.  Follow-up imaging one year later revealed no evidence of recurrence or residual tumor.  This patient case underscores the importance of recognizing signs and symptoms of serious disease, and how referral following telehealth via telephone can inform diagnosis.